ASSESSING FAMILY PLANNING SERVICE QUALITY AND USER EXPERIENCES IN SOCIAL FRANCHISING PROGRAMME - CASE STUDIES FROM TWO RURAL DISTRICTS IN PAKISTAN - Azmat, Syed Khurram; Ali, Moazzam; Hameed, Waqas; Awan, Muhammad Ali (Journal of Ayub Medical College Abbottabad, 2018)
Background: Studies have documented the impact of quality family planning services on improved contraceptive uptake and continuation, however, relatively little is known about their quality of service provision especially in the context of social franchising. This study examined the quality of clinical services and user experiences among two models in franchised service providers in rural Pakistan. Methods: This facility-based assessment was carried out during May-June 2015 at the 20 randomly selected social franchise providers from Chakwal and Faisalabad. In our case, a franchise health facility was a private clinic (mostly) run by a single provider, supported by an assistant. Within the selected health facilities, a total 39 user-provider interactions were observed and same users were interviewed separately. Results: Most of the health facilities were in the private sector. Comparatively, service providers at Greenstar Social Marketing/Population Services International (GSM/PSI) model franchised facilities had higher number of rooms and staff employed, with more providers' ownership. Quality of service indices showed high scores for both Marie Stopes Society (MSS) and GSM/PSI franchised providers. MSS franchised providers demonstrated comparative edge in terms of clinical governance, better method mix and they were more user-focused, while PSI providers offered broader range of non-FP services. Quality of counselling services were similar among both models. Service providers performed well on all indicators of interpersonal care however overall low scores were noted in technical care. For both models, service providers attained an average score of 6.7 (out of the maximum value of 8) on waste disposal mechanism, supplies 12.5 (out of the maximum value of 15), user-centred facility 2.7 (out of the maximum value of 4), and clinical governance 6.5 (out of the maximum value of 11) and respecting clients' privacy. The exit interviews yielded high user satisfaction in both service models. Conclusion: The findings seem suggesting that the MSS and GSM/PSI service providers were maintaining high quality standards in provision of family planning information, services, and commodities but overall there was not much difference between the two models in terms of quality and satisfaction. The results demonstrate that service quality and client satisfaction are an important determinant of use of clinical contraceptive methods in Pakistan. Keywords: Family planning; Pakistan; Rural; Service quality